Prevalence of colorectal carcinoma based on microscopic type, sex, age and anatomical location in Sanglah General Hospital - Michelle Anne Anthonysamy; Luh Putu lin Indrayani Maker; I Made Gotra; Herman Saputra (DiscoverSys Inc., 2020)
Background: Colorectal carcinoma (CRC) is a disease in which epithelial cells in the colon or rectum become abnormal and divide without control, forming a mass called a tumor. Colorectal carcinoma is the fourth most frequent cancer in men after prostate and lung or bronchus cancers whereas in women is the third most frequent cancer after breast and lung or bronchus cancers. Colorectal cancer is a leading cause of cancer death worldwide, accounting for 693,900 deaths in 2012 and is the fourth most frequent cancer in men whereas in women is the third most frequent cancer. In Indonesia amount of rectal cancer were 1407 (5.67%) and 990 cases (3.99%) of colon cancer. Specifically in Denpasar, there are a total of 75 cases (7.11%) of rectal cancer and 38 cases (3.60%) of colon cancer in the year.Aim: This study aims to know the prevalence of colorectal carcinoma based on microscopic type, sex, age and anatomical location in Sanglah General Hospital in Denpasar from January 2014 to January 2016.Method: This study used descriptive retrospective research based on the secondary data from patients medical record which was taken at Sanglah General Hospital from January 2014 to January 2016. Population and sample amounted to 275 patients.Results: This study shows that the highest prevalence of colorectal carcinoma was in a group of age <50 years old with 86 samples (31.3%) and in a male with 163 samples (59.3%). Adenocarcinoma has the highest prevalence of colorectal carcinoma with 270 samples (98.2%). The rectum was the most frequent tumor location with 170 samples (61.8%). In adenocarcinoma, the age group with the highest prevalence of CRC was <50 years with 85 samples (30.9%). The highest prevalence of CRC based on anatomical location and age group was <50 years in the rectum with 57 samples (20.7%).Conclusion: Most of the CRC was found in age group < 50 years, men had a higher risk to get colorectal carcinoma, adenocarcinoma is the most common microscopic type, and rectum was the most common site of colorectal carcinoma.